#TITLE_ALTERNATIVE# - RADITYA (NIM 15107084); Pembimbing: Dr. Deni Suwardhi, ST.,MT. dan Dr.Ir. Agung Budi Harto, M., FERDI
Small Format Aerial Photogrammetry (SFAP) is one of mapping method that is being developed at this time. This method has advantages in terms of a relatively easy to get the mapping equipment and operating costs are cheaper than a standard aerial photographs. In order to provide spatial information, this photo image needs to be done by photogrammetric processing which consists of several stages. One of the stages required ground control points as reference. This thesis will examine how to improve the accuracy of the photogrammetric process from bundle adjustment stage by using two variables change, the number of images and the number of ground control points (GCP). This research is divided into 3 phases, there are planning and preparation, field data collection and processing the data. Planning and preparation includes the preparation of equipment / materials and the determination of flight paths. Field operations include ground control point data collection and recording the aerial photographs. Processing the data steps include GPS data processing and bundle block adjusment of aerial photographs. The results showed that the bundle adjusment on the block by adding the number of cross flight image did not improve the accuracy, it can be seen from the RMSE which is increase. While the experiment by adding the number of ground control points from 3 points to 10 points, there is an increasing accuracy but when at the addition of 15 points, the result is decreasing.